Coagulation tests or standardized questionnaire, which is better as a predictor of bleeding? A prospective study among children before tonsillectomy and/or adenoidectomy - Muhamed Masalha; Ari DeRowe; Salim Mazzawi; Tzvi Chen; Rami Ghanayim; Roee Landsberg; Ariel Koren (BMC Research Notes, 2020)
Abstract Objective The value of pre-operative coagulation testing for adenotonsillar surgery is controversial. The purpose of this study was to evaluate the role of routine coagulation tests and a standardized questionnaire in children before tonsillectomy and/or adenoidectomy. Results A total of 143 children were prospectively enrolled in the study between 2013 and 2017, 81 males (56.6%) and 62 females (43.4%), age range 1 to 18 years (median age 5 years). Eighteen bleeding events were documented, three of them required treatment in the operating room. Abnormal coagulation tests were not associated with higher odds of bleeding after surgery. Higher risk of bleeding (p = 0.01) was associated with an abnormal standardized medical questionnaire.